A steganography embedding method based on CDF-DWT technique for data hiding application using Elgamal algorithm. (February 2023) - Sashi Rekha, K.; Joe Amali, Miruna; Swathy, M.; Raghini, M.; Priya Darshini, B.
Highlights: Cohen-Daubechies-Feauveau Discrete Wavelet Transform (CDF-DWT) technique for data hiding applications using the Elgamal Algorithm. The secret data is hidden in the cover image to get the stegano image by embedding using the CDF-DWT technique. Steganography has increased embedding efficiency, embedding capacity, carrier capacity and reduced execution time. Abstract: Steganography is a data hiding method used for security purposes. While hiding more data in the embedding process, the data may be lost and cause some security problems. The steganography embedding method is used to avoid this problem. In this manuscript, the steganography embedding method is proposed based on the Cohen-Daubechies-Feauveau Discrete Wavelet Transform (CDF-DWT) technique for data hiding applications using the Elgamal algorithm. The cover image is considered to hide the secret data and then the cover image edges are detected and filtered by using the Speeded-Up Robust Features (SURF) method. Elgamal algorithm is used to encrypt the input data. This method aims to safeguard the secret data using the steganography method with increase on embedding efficiency, embedding capacity, carrier capacity and reduce execution time. The proposed CDF-DWT technique with Elgamal algorithm shows better results with Peak to signal noise ratio (PSNR) of 45.78%, Mean Square Error (MSE) of 2.09%, and Bit Error Rate (BER) of4.56%, the execution time of 5.98%, Carrier Capacity of 85.90% and Embedding Capacity of 80.67%. The obtained values are compared with the existing state-of-the-art method in data hiding.